“SUBJECT GENERALITY” AND DISTRIBUTION IN MEDIEVAL ARABIC SYLLOGISTIC - El-Rouayheb, Khaled (Arabic sciences and philosophy : a historical journal, 2023)
A relatively well-known medieval Latin innovation is the doctrine of distributive supposition. This notion came to be used in syllogistic theory in the late medieval and early modern periods, as Latin logicians sought to establish general rules for syllogistic productivity across the various figures. It is much less well-known that some logicians in the medieval Arabic tradition also attempted to establish general rules for the syllogism, appealing to what they called “subject generality.” In the present article, I introduce this use of “subject generality” in some influential Arabic works on logic from the thirteenth century to the sixteenth, specifically Al-ǧumal by Afḍal al-Dīn al-Ḫūnaǧī (d. 1248) and Tahḏīb al-manṭiq by Saʿd al-Dīn al-Taftāzānī (d. 1390) and some of their commentators. I also compare this concept of “subject generality” to the Latin concept of “distribution.”